Same Goal, Different Paths, Different Class: Women’s Feminist Political Engagements in Kosovo from the Mid-1970s until the Mid-1990s - Krasniqi Elife (Comparative Southeast European Studies)
The year 1989, when Serbia revoked Kosovo’s autonomy, was a break that changed also the course of women’s political engagements. Women had always to negotiate and strategise with different layers of power and against different forms of oppression—state and patriarchal oppression and cultural racism as well as class oppression. The author highlights the convergences and divergences of women’s political activism in the political dynamics of late socialism and then in the 1990s in Kosovo. She looks at gender, class and national dimensions of women’s political engagements with a focus on women who were part of the underground resistance movement commonly known as Ilegalja in the 1970s and 1980s as well as women intellectuals who held high state positions and were considered a part of the elite. After 1989, many engaged in the peacaful resistance movement of the 1990s.